2017
DOI: 10.1177/1526602817748316
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lesion Morphology on Durability After Angioplasty of Failed Arteriovenous Fistulas in Hemodialysis Patients

Abstract: The patterns of AVF stenosis as determined by ultrasound can affect the outcome of treatment with balloon dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…VA, vascular access; DSA, digital angiography; PTA, percutaneous transluminal angioplasty. (7,16,17).…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…VA, vascular access; DSA, digital angiography; PTA, percutaneous transluminal angioplasty. (7,16,17).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…PTA can restore the flow of occluded vascular vessels, with a success rate of 80-100% (5). And it is an established treatment for stenosis in both AVFs and AVGs, which can significantly extend the patency duration of fistulas (6,7). However, as a result of recurrent stenosis, repeated interventions have often been required, with a reported average of 3.1-3.5 times before access is ultimately abandoned (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Suemitsu et al in 2017 described three types of stenosis based on ultrasound appearances; an intimal hyperplasia type, a shrinking type and a valve type. They reported that a shrinking lumen morphology had a negative impact on primary patency at 6 months following percutaneous angioplasty (HR 2.05, 95% CI 1.25–3.36, p = 0.005) and a venous valve type stenosis had a positive impact on primary patency (HR 0.19, 95% CI 0.04–0.79, p = 0.023) 9 . Both these studies suggest that the type of AVF stenosis assessed on ultrasound may affect patency rates after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al [17] described a cohort of 46 AVG outflow stenosis cases whose lesions were divided into 3 groups by DU evaluation: vascular constriction types (13/46, 28.3%), neointimal proliferation types (12/46, 26.1%), and mixed types (21/46, 45.7%); the vascular constriction type in their study displayed excellent primary patency rates after stent treatment. Suemitsu et al [18] investigated 158 AVF venous lesions and divided them into 3 stenosis patterns by ultrasonography: intimal hyperplasia stenosis (110/158, 69.6%), shrinking lumen stenosis (32/158, 20.3%), and venous valve-related stenosis (16/158, 10.1%). In their analysis, the AVF stenosis pattern affected the outcome after PTA; the shrinking lumen morphology had a negative impact on primary patency (HR 2.05, 95% CI 1.25–3.36, and p = 0.005), while the venous valve-related stenosis had a positive impact (HR 0.19, 95% CI 0.04–0.79, and p = 0.023).…”
Section: Discussionmentioning
confidence: 99%